Cardiac pacing, defibrillation and resynchronization : a clinical approach - Asirvatham, Samuel J.; Friedman, Paul A.; Hayes, David L. (New Jersey : Wiley-Blackwell, 2021)
"In many ways, this textbook mirrors the development of the field of cardiac device placement and management. The original version of this text was written by Drs. Seymour Furman, David Hayes, and David Holmes, pioneers and founders of interventional electrophysiology and device management. The goals of the present text remain similar to the original intent, that is, to provide a relatable, practical approach without ignoring the rigors of fundamental principles while retaining the flexibility in the professional's mind to embrace new technology. Updates on resynchronization therapy, subcutaneous defibrillators, leadless devices, and improvements in lead extraction have been included in this text. We continue to stay away from an encyclopedic approach but rather focus on a usable, practical, and intuitive approach for problem solving in the day-to-day practice of a cardiac electrophysiology professional. As with all prior editions, we owe a great debt of gratitude to all the contributors who have tirelessly updated their sections and have done multiple revisions. We also have to thank our patients and nursing staff who provide us with material to allow us to learn to a point where we can try and teach troubleshooting approaches, etc. We received tremendous support from various device manufacturers, their engineers, and their published data material. These include assistance from Biotronik, Boston Scientific, Medtronic, and Abbott Medical"--
BIBINDX
Keywords: Cardiac Pacing, Artificial -- methods; Defibrillators, Implantable; Pacemaker, Artificial; Electronic books